The Importance of Great Women’s Leadership as Primary Educators in Families - Ma’rifah, Siti; Arifin, Antoni Ludfi; Syarief, Abdul Ghofar; Pranogyo, Antaiwan Bowo (Graduate Program Magister Manajemen Pendidikan, 2023)
Based on the findings of a literature research, this article intends to investigate the leadership qualities of a great woman as an educator in the family as perceived through the six value elements of humility, excitement, establishing competences, agility, and tactful. Changes in the millennial period now require that women have equal rights as males in all aspects of life. Women’s successes and skills to date have reinforced the assumption that there are little distinctions between men and women. Women’s leadership and role as primary educators in the home demonstrate their accomplishments and talents. According to the findings of a literature review from various sources, a great woman is a family leader because she is the one who can effectively manage household affairs, raise and educate children in the family, and provide input and suggestions to her husband as part of her role as a family educator.